A new indicator of ecosystem water use efficiency based on surface soil moisture retrieved from remote sensing. (April 2017) - He, Bin; Wang, Haiyan; Huang, Ling; Liu, Junjie; Chen, Ziyue
Abstract: Ecosystem water use efficiency is an important indicator of carbon and water cycle coupling. This study presents a new measure of water use efficiency, soil water use efficiency (SWUE), based on gross primary production and surface soil moisture derived from remote sensing products (ECV-SM). Variation in SWUE among biomes, climate conditions, and latitudes from 2000 to 2014 was comprehensively assessed. Average global SWUE over this 15-year period was approximately 3.47 gC/kgH2 O. SWUE was relatively high for ecosystems near the equator and decreased gradually with increasing latitude. At the biome level, high SWUE was measured in evergreen broadleaf forests, and lower values were found in shrublands. Compared with two other commonly used indicators of water use efficiency, EWUE (ratio of gross primary production to evapotranspiration) and RUE (ratio of gross primary production to precipitation), average SWUE from 2000 to 2014 was significantly higher and had the largest range of values. In addition, spatial distributions of these three indicators varied greatly. The new indicator SWUE will help promote understanding of soil water use in various ecosystems.